REFLEKSI MATA KULIAH PRAKTEK KEPENDIDIKAN LAPANGAN MATA PELAJARAN EKONOMI DI MAN 2 MERANGIN - Eyyah Haririyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Field Education Practice (PKL) is a scholastic task designed to give future teachers practical experience in executing the learning process within a school setting. This article reflects on the execution of PKL in the Economics subject at MAN 2 Merangin, covering the phases of observation, preparation of lessons, teaching delivery, and assessment of the outcomes of the practice. By having firsthand experiences in the classroom and engaging with students and mentor instructors, the writer developed a greater insight into methods of learning, managing the classroom, creating teaching resources, and evaluating educational results. This contemplation reveals that PKL significantly contributes to the growth of future teachers' teaching, professional, social, and personal skills. Furthermore, the outcomes of this contemplation also highlight the necessity of creativity, communication abilities, and adjusting to student traits to enhance the effectiveness of Economics education. This piece is anticipated to act as a guide for future education students in getting ready to approach the education field with greater maturity and professionalism.